Analysis of smile pattern at a tertiary care centre - Joshi, Kalit Raj; Shrestha, Anupama; Khanal, Lok Raj; Guragain, Manjeev; Bhochhibhoya, Amar; Maskey, Suvit; Khanal, Shishtata (Journal of Kathmandu Medical College, 2022)
Background: The treatment of the aesthetic region of mouth is complicated. Knowledge of the smile pattern which includes smile line, smile curvature, smile arc, labiodental relation, and tooth exposed determines the success of treatment. This is helpful in the diagnosis and treatment planning phases of aesthetic dentistry. Objectives: To determine the smile pattern in aesthetic region and to compare the different smile patterns. Methods: This analytical cross-sectional study was done in the department of Prosthodontics and Maxillofacial Prosthesis, Universal College of Medical Sciences, Nepal from 15th October 2021 to 15th March 2022. A total number of 355 samples were taken by convenience sampling technique. After receiving participant’s consent, study was carried out using a digital camera. The camera was set to primarily capture the area between nose and chin, with lens parallel to the apparent occlusal plane of the participants. For study purpose, individuals were told to sit and hold head normally with their head in level with Frankfort horizontal plane. Results: The total number of participants were 355 out of which 153 (43.09%) were male and 202 (56.91%) were female. In the smile line pattern, the “Average” smile line was prevalent in a maximum number of participants (223, 62.8%) followed by the high and low smile lines. There was a significant relationship between the smile arc, labiodental relationship, and the tooth displayed. Conclusion: The findings of this study determines the smile pattern of this region, thus this will be helpful in the diagnosis and treatment planning during the treatment.